The Effect of St. John’s Wort Oil on Urethral Stricture: An Experimental Study in Rat Model - Kazım Yelsel; Ergün Alma; Ömer Yüceer; Zeynel Abidin Taş; Berna Totan Ateş; Murat Kobaner; Halil Esimek; Adem Altunkol; Umut Ünal; Ali Ayyıldız (Urology Research and Practice)
Objective: The aim was to evaluate the effect of yellow and red centaury St. John’s Wort (St. JW) oil on inflammation and urethral fibrosis development in a rat urethral trauma model.